Synthesis of β-Silicon carbide nanowires by a simple, catalyst-free carbo-thermal evaporation technique - Al-Ruqeishi, M.S.; Nor, R.M.; Amin, Y.M.; Al-Azri, K. (2012)
β-SiC nanowires were successfully fabricated on pare Si (100) substrate using simple carbo-thermal evaporation of graphite at 1200Â°C. The obtained β-SiC nanowires were aligned with diameters ranged between 40 to 500 nm. The majority of crystal planes were β-SiC (111) with other less intensity of (200), (220) and (311). The silicon substrate location inside the furnace found to be critical in the formation of the β-SiC nanowires. Also, FTIR absorption peaks for β-SiC nanowires found at higher frequency side of 1110 cm-1 which is pointed to Si-O asymmetric stretching mode. Â© 2012 Penerbit UTM Press. All rights reserved.